Perbuatan Melawan Hukum Oleh Pemerintah Dalam Pengadaan Barang/Jasa Pemerintah Di Lingkungan Kementerian Perhubungan Republik Indonesia (Studi Kasus Putusan PTUN Medan Nomor: 4/P/FP/2020/PTUN-MDN dan Putusan PN Medan Nomor: 465/Pdt.G/2020/PN Mdn) - Rapen A.M.S Sinaga; Gindo L Tobing; Wiwik Sri Widiarty (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Development is an important sector to achieve the goals of developing countries like Indonesia. In its development, development continues to be planned every year to support the development of the Indonesian economy. Procurement activities of goods and services in the development process often give rise to negative implications in very complicated legal issues. A conspiracy is an unlawful act by officials implementing goods and service procurement activities between procurement officials and providers of goods and services to play cheating and not in accordance with the objectives, principles, policies, and ethics of government procurement of goods and services. The formulation of the problem in this research is 1) how to find out legal protection for PT. Putri Mahakam Lestari, who had been named the winner of the tender, was unable to carry out the work, even though the Medan PTUN and Medan District Court had strengthened PT. Putri Mahakam Lestari as the tender winner; 2) what is the state's responsibility for unlawful acts committed by government officials, which have been decided by the Medan State Administrative Court Number 4/P/FP/2020/PTUN-MDN and the Medan District Court Number 465/Pdt.G/2020/PN Mdn. This research uses normative juridical research with a descriptive approach through legislation and a case approach. From the research results it was found that in accordance with Article 53 paragraphs (1) and (2) of Law no. 30 of 2014 concerning Government Administration, PT. Putri Mahakam Lestari as the winner of the tender should receive a Letter of Appointment as Provider of Goods/Services (SPPBJ) and carry out the contract based on Government Goods/Services Procurement Policy Institute Regulation No. 9 of 2018 concerning Guidelines for Implementing Procurement of Goods/Services through Providers for Determining Winners and Regulation of the Minister of Public Works No. 07 of 2019 concerning Standards and Guidelines for Procurement of Construction Services through Providers, Preparatory Meeting for the Appointment of Providers, Article 91 paragraph (1) regarding the construction of the Estuary Ferry Port phase III. Then, as a state responsibility, it must be in accordance with the regulations regarding sanctions in the procurement of government goods and services regulated in Articles 78 - 82 of Presidential Regulation Number 16 of 2018 concerning Procurement of Government Goods/Services in conjunction with Presidential Decree No. 12 of 2021 concerning Government Procurement of Goods/Services including allegations of conspiracy and attempts to abuse the authority of UKPBJ, PPK and KPA provide: 1) the sanction of being aborted in the election; 2) sanctions for disbursement of collateral; 3) Blacklist Sanctions; 4) compensation sanctions; 5) fine sanctions; 6) sanctions for temporary suspension in the E-purchasing transaction system; and/or 7) sanctions for reducing the provider's inclusion in the electronic catalog. ASN/Government Officials in Procurement/Election Working Group/Procurement Agents who are proven to be involved in conspiracy may be subject to sanctions based on Law Number 5 of 2014 concerning State Civil Apparatus and Law Number 20 of 2001 concerning Amendments to Law Number 31 of 2014. concerning the Eradication of Corruption Crimes.